Norton Dudeque, Music Theory and Analysis in the Writings of Arnold Schoenberg (1874-1951) (2005) - Heneghan, Áine (Journal of the Society for Musicology in Ireland, 2008)
A review of Norton Dudeque, Music Theory and Analysis in the Writings of Arnold Schoenberg (1874-1951) (Aldershot and Burlington, VT: Ashgate, 2005), ISBN 0754641392, xv + 274 pp, £55.00/$99.95.